Experimental Evaluation of the Average Energy for Impact Ionization by Holes in Al0.4Ga 0.6N Alloy - Haifeng Chen; Yiren Chen; Hang Song; Zhiming Li; Hong Jiang; Dabing Li; Guoqing Miao; Xiaojuan Sun; Zhiwei Zhang (IEEE Photonics Journal)
An experimental approach to evaluate the average energy required by holes for impact ionization in Al0.4 Ga0.6N alloys is presented. A series of back-illuminated separate absorption and multiplication structures with different thickness of multiplication layer are employed. With the measured quantum efficiency of devices and a consideration of energy conservation in ionization process, the average energy for electron-hole pair production by energetic holes is obtained and it qualitatively agrees with the bond energy of Al0.4Ga0.6N, which is estimated from the Vegard's law.